(( The effect of an educational field with a sensory electronic system on some harmonious abilities in futsal for youth )) (Journal of the College of Basic Education, 2023)
The study aimed to prepare exercises within the educational field using a sensory electronic system in developing some abilities in futsal as well as identifying The effect of these exercises on the development of these abilities for futsal athletes, the researcher assumed several hypotheses, including the existence of statistically significant hypotheses between The results of the pre and posttests in all the research variables refer to the test of the youth players of the Baghdad group in the youth league for the year 2022-2023 and their number was (90) players as a community for his research, then he chose two teams from the seven teams of the Baghdad Group for the Youth League as a sample for his research, and he chose (10) players from each team to form two groups One of them is experimental and the other is control, and the percentage of the sample to the community is (22%). The experimental group was given exercises in the educational field using the electronic system. Sensory and auxiliary tools. The duration of the main experiment lasted (12) weeks, with an average of (12) educational units, the time of each unit was (90) minutes. After that, the tests were conducted. The dimension of the harmonious abilities of futsal for the halls and the spss statistical bag system was used in the process of processing the results of the pre and posttests, and the researcher reached to A number of conclusions, the most important of which was that the exercises prepared and designed by the researcher within the educational field of the sensory electronic system were effective in developing some The harmonious capabilities of the research sample that was applied to it, and I recommend taking the results of this study and benefiting from them in developing the educational units in futsal football for the youth clubs of the Baghdad group.